An Evaluation into the Physical Activities of Housewives at Different Educational Level (Case of Amasya) - Editor, İskender Güler (Journal of Educational Issues, 2024)
The main premise of this paper is to examine the physical activities of housewives at different educational level in the center of Amasya Province. A total of 340 volunter housewives from different socioeconomic status were randomly recruited. We collected the data through the Physical Activity Assessment Questionnaire (PAAQ). We employed descriptive statistics, including mean, standart deviation, minimum and maximum values, frequencies and percentages regarding physical qualities and activities. We performed the a Pearson Correlation Analysis to evaluate the relationships between physical qualities and activities. Based on the statistics, the distribution of the weekly activities of the participants are as follows: 44.4% of housewives walking, 8.8% jogging, 80.0% housework, 51.8% shopping, 52.4% climbing up stairs (40 steps or less). 2.4% doing step-aerobic activities, 24.1% babysitting, 2.6% using a computer and 52.2% watching television. Further, we found that as the education level of housewives increased, their use of cars and reaching a destination on foot increased (p < 0.05, p < 0.01); that BMI levels decreased significantly (p < 0.01) with the increase in education levels, working days and on foot transportation, and BMI levels increased (p < 0.01) with the increase in passive recovery times. In conclusion, it can be suggested that housewives in Amasya have some levels of physical activities to some extent, but these activities are mostly walking, shopping, babysitting and doing households.